Reconstructing Individualism : A Pragmatic Tradition from Emerson to Ellison - Albrecht, James M. (Book collections on Project MUSE., 2012)
"Explores the theories of democratic individualism articulated in the works of the American transcendentalist writer Ralph Waldo Emerson, pragmatic philosophers William James and John Dewey, and African-American novelist and essayist Ralph Ellison"--